O conteúdo valorativo da norma jurídica: a fenomenologia do direito e os valores axiomáticos para uma juridicidade concretista da administração pública - Dezan , Sandro Lúcio (2018)
The present thesis investigates the sub-content of the legal norm, through the phenomenology of the Right, to the point of establishing a tripartite qualitative structure, in a relation not of cogenerality, but rather of specialty of this instrument of social regulation. Regarding traditional concept of specialty between principles and legal rules, that is, a strong dual and qualitative formation between principles and rules, the phenomenology of the Law leads to the calibration of normativity, also, of the values, that come to compose, together with the other two species, the deontic character of Law. It can be seen that the axiological values, in the spectrum of real history, in the fusion of horizons and in the tradition, are segmented into the perception of an axiomatic stratum, which, in fact, presents a naturally deontic essence within a particular sociocultural context, time-localized, adding to the other normative species. However, in spite of a pre-understanding of the values presented in the nature of legal principles and, thus, being confused and characterized by a dimension of weight, the research shows that they are qualitatively distinct categories, whereas it is maintained that legal values have a nature of validity. Axiomatic values, therefore, operate in the same way as the legal rules, as the commandments of concreteness, in an all-or-nothing way, without, however, being confused with the rules, as long as they stand as the basis for their validity, and also of legal principles. For these findings, it is essential to use Heidegger's phenomenology applied to law (hermeneutical philosophy), Gadamer's philosophical hermeneutics and argumentative hermeneutics, as a means of revealing the phenomena in vogue. We conclude that values, principles and rules are species of the genus "legal norm", where values are located at the base of the normative system, for the foundation of principles and of rules.